Pengembangan Digitalisasi Desa dalam Mewujudkan Transformasi Smart Village di Desa Banjarsari Kabupaten Jombang - Hazin, Mufarrihul; Yani, Muhammad Turhan; Haq, Mohamad Syahidul (Journal of Smart Community Service, 2025)
The development of village digitalization is an important strategy in building the foundation of a Smart Village, a paradigm of rural development that is innovative, connected, and technology-based. The Community Service Program (PKM) in Banjarsari Village, Jombang, aims to (1) identify the challenges of village digitalization, (2) design solutions for digital transformation, and (3) develop a digital village application as a medium for public services and community empowerment. The method used was Participatory Action Research (PAR) with stages of diagnosis, mapping, action, observation, and reflection. The results of the program include the development of the banjarsari.desabaik.id application, training for village officials, and digitalization socialization to the community. Evaluation shows that the majority of training participants felt more familiar with the concept of digitalization, gained a better understanding of the benefits of technology, and increased their confidence in using the application and the village’s social media. This program has proven effective in improving administrative services, transparency, and local economic potential. Nevertheless, challenges such as limited internet infrastructure and resistance from some community members still need to be addressed through continuous mentoring. The results of this PKM indicate that village digitalization is a strategic step toward inclusive, adaptive, and competitive rural development